Simulation-Based Mock-Up Evaluation of a Universal Operating Room. (January 2020) - Shultz, Jonas; Borkenhagen, David; Rose, Emily; Gribbons, Brendan; Rusak-Gillrie, Hannah; Fleck, Shelly; Muniak, Allison; Filer, John
Designing or renovating a physical environment for healthcare is a complex process and is critical for both the staff and the patients who rely on the environment to support and facilitate patient care. Conducting a simulation-based mock-up evaluation as part of the design process can enhance patient safety, staff efficiency, as well as user experience, and can yield financial returns. A large urban tertiary care center located in Vancouver, Canada followed a framework to evaluate the proposed design template for 28 universal operating rooms (ORs) included within the OR Renewal Project scope. Simulation scenarios were enacted by nursing staff, surgeons, anesthesiologists, residents, radiology techs, and anesthesia assistants. Video and debriefing data were used to conduct link analyses, as well as analyses of observed behaviors including congestions and bumps to generate recommendations for evidence-based design changes that were presented to the project team. Recommendations incorporated into the design included relocating doors, booms, equipment, and supplies, as well as reconfigurations to workstations. These recommendations were also incorporated into the mock-up and retested to iteratively develop and evaluate the design. Findings suggest that incorporating the recommended design changes resulted in better room utilization, decreased congestion, and enhanced access to equipment.